Nitrous oxide: a unique official French addictovigilance national survey - Guerlais, Marylène; Aquizerate, Aurélie; Lionnet, Arthur; Daveluy, Amélie; Duval, Mélanie; Gérardin, Marie; Istvan, Marion; Laforgue, Edouard-Jules; Victorri-Vigneau, Caroline; , for French Addictovigilance Network (Frontiers in Public Health, 2023)
Introduction Nitrous oxide has become over the last few years a public health problem in many countries. France has a dedicated health monitoring system dedicated to the surveillance of the abuse, dependence and consequences associated with the use of psychoactive substances coordinated by the French National Agency for the Safety of Medicines and Health Products. We present the French national survey of nitrous oxide. Materials and methods We analyzed all the cases with nitrous oxide from 2012 to 2021: number of notifications, characteristics of the subjects and consumption, consequences reported and their evolutions over time. In addition, we have made a special focus on the four main complications reported. Results A total of 525 cases were received with an exponential increase since 2019. We observed changes in the characteristics of the notifications with an increase in the proportion of women [42.7% in 2021 vs. 30.8% in 2020 (p = 0.02)]; an increase in the quantities consumed (use of cylinders); a negative evolution of the contexts of use with a search for self-therapeutic effects and use in violent contexts; an increasing trend of the severity of cases [78.1% in 2021 vs. 70.0% in 2020 (p = 0.07)]. The main effects were substance use disorders and/or associated criteria (82.5%), neurological disorders (75.4%), psychiatric symptoms (15.4%) and cardiovascular events (8.6%). In terms of evolution, we observed a significant increase in cases with a use disorder and an increase in neurological complications. Moreover, new serious effects, notably cardiovascular events were reported. Discussion The combination of high availability, varied effects from euphoria to relief of discomfort in a stressful global pandemic context and the development of dependence could explain the rapid growth of consumption and the seriousness of the cases. It must now be taken into account that (i) Substance use disorders are associated with nitrous oxide consumption; (ii) clinicians must consider “nitrous oxide” in young subjects presenting different types of manifestations; and (iii) stopping consumption is imperative and is the first treatment. In this context, an addictological assessment must also be carried out.